Dynamics of 137Cs accumulation by herbaceous plants on peat-bog soils with abnormally high bioavailability - I. M. Maloshtan; S. V. Polishchuk; Yu. V. Homutinin; V. A. Kashparov (Ядерна фізика та енергетика)
Dynamics of bioavailability of freshly introduced 137Cs has been studied in 2-year lab experiments for peat-bog soils of Rokytne district of Rivne region. The obtained parameters of dynamics of root accumulation of 137Cs by herbaceous plants in peat soils with abnormally high bioavailability differ from those previously reported in the literature. Fast period of half-reduction of the concentration ratio of 137Cs was 0.2-0.3 year, and the concentration ratio reached the stable level in 1-2 years. Ratio of the fast to slow components of the concentration ratio extrapolated at the moment of radiocesium injection into soil was estimated as 4-5.